Perlindungan Warga Sipil Dalam Konflik Bersenjata (Studi Kasus Penggunaan Asas Pembedaan Dalam Konflik Di Suriah) - Lesza Leonardo Lombok; Angel Christi Singkoh; Yolanda Salainti (Lembaga Penelitian Pengabdian Masyarakat dan Pusat Kajian - Universitas Ngurah Rai, 2025)
This study aims to examine the protection of civilians in the armed conflict in Syria through the application of the principle of distinction under International Humanitarian Law. This principle requires conflicting parties to differentiate between combatants and civilians, as well as between military targets and civilian objects. However, in practice, violations frequently occur, resulting in high civilian casualties. The research also aims to analyze the content of the 1949 Geneva Conventions and the 1977 Additional Protocols. The findings indicate that despite the existence of international legal regulations providing protection, violations remain widespread. Therefore, the study recommends strengthening international oversight, enhancing humanitarian law education, and enforcing strict sanctions against violators to improve the protection of civilians